The Effect of Facebook Addiction on the Identity Crisis of the University Student - Senouci Boumediene; Djellouli Zineb; M. Yoserizal Saragih (Budapest International Research and Critics University, 2020)
The study aimed to reveal the impact of Facebook addiction on the identity crisis of the university student, and to know the relationship between internet addiction and identity crisis in its various dimensions (concept of self, self-esteem, direction towards the other, school and professional tendencies) of the university student. The study sample consists of (91) university students, and to achieve the objectives of the study two research tools have been used: the first is internet addiction scale developed by 'Ahmed' (2007), and the second is the identity crisis scale developed by the following researchers: 'Shand, Mohammed Samira and Shaheen, Iman Fawzi and Private, Hadi Hassan Raafat' (2015). To reveal the identity crisis and after collecting and processing information statistically using the Statistical Package for Social Sciences (SPSS) and R program, the researchers reached the following conclusions: The coefficient of correlation between the concept of self and Facebook addiction is statistically significant. The coefficient of self-esteem and internet addiction is statistically non-significant. The correlation coefficient between the other direction and internet addiction is statistically non- significant. The correlation coefficient between school and occupational tendencies and Internet addiction is statistically significant. Internet addiction affects the concept of self. Internet addiction does not affect self-esteem. Internet addiction does not affect the trend towards the other. Internet addiction does not affect school and professional tendencies.